UPAYA PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT - Yohanes Kaha (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: Human resources are the main factor for the sustainability of an organization. Empowerment of Human Resources is an activity or activity carried out so that human resources within the organization can be used to achieve the goals of the organization. The type of research used in this study is qualitative research, with focus namely; empowerment of the education sector, economic sector and inhibiting and supporting factors in efforts to empower human resources, data collection techniques, namely observation, interviews, documentation, data analysis techniques, namely: data presentation, data reduction and conclusion drawing. The results of research efforts to empower human resources in the education sector is to approach and provide recommendations for continuing education, the economic sector that is providing assistance in the form of cabinets, making it easier for submissions to banks and cooperatives. Inhibiting factors in the empowerment efforts in the education sector namely; there is still a lack of interest for advanced schools so that education is limited at the junior / senior high school level. Supporting factors include having a 1-roof junior high school building and an elementary school located in one complex, with students coming to school in Gunungsari village. Inhibiting factors in the effort to empower human resources in the economic sector are weather (dry season), and poor road access, markets that are still far away. Supporting factors are providing assistance to the elderly, widows and those who can.  Keywords: Village Government, Community Empowerment Abstrak: Sumber daya manusia merupakan faktor utama bagi keberlangsungan sebuah organisasi. Pemberdayaan Sumber Daya Manusia merupakan aktivitas atau kegiatan yang dilaksanakan agar sumber daya manusia didalam organisasi dapat dipergunakan untuk mencapai tujuan organisasi tersebut.Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif, dangan focus yaitu; pemberdayaan sector pendidikan, sektor ekonomi dan factor penghambat dan pendukung dalam upaya pemberdayaan sumber daya manusia, teknik pengambilan pengumpulan data yaitu observasi, wawancara, dokumentasi, teknik analisa data yaitu: penyajian data, reduksi data dan penarikan kesimpulan. Hasil penelitian upaya pemberdayaan sumber daya manusia sector pendidikan yaitu melakukan pendekatan secara dan memberikan rekomendasi untuk melanjutkan pendidikan, sector ekonomi yaitu memberikan bantuan berupa rak lemari, mempermudah untuk pengajuan ke bank dan koperasi. Faktor penghambat dalam upaya pemberdayaan disektor pendidikan yaitu; masih kurangnya minat untuk sekolah lanjut sehingga, pendidikan terbatas ditingkat SMP/SMA.Faktor pendukung yaitu sudah memiliki gedung SMP 1 atap dan SD yang terdapat dalam 1 kompleks, adanya pelajar yang dating bersekolah didesa Gunung sari. Faktor penghambat dalam upaya pemberdayaan sumber daya manusia disektor ekonomi yaitu cuaca (kemarau), dan akses jalan yang kurang baik, pasar yang masih jauh.Faktor pendukung yaitu memberikan bantuan kepada lansia, janda dan yang mampu. Katakunci: Pemerintah Desa, Pemberdayaan Masyarakat.